Pengaruh Seleksi Dan Penempatan Terhadap Kinerja Karyawan Pada PT Suzuki Finance Indonesia Kantor Pusat Jakarta - Riyadi, Didi Slamet; Vikaliana, Resista (Jurnal MBE Manajemen Bisnis, Equilibrium, 2020)
The main problem in this study was suboptimal employee performance in PT Suzuki Finance Indonesia, so that it was suspected that selection and placement affected employee performance in the Jakarta Headquarter of PT Suzuki Finance Indonesia. The research type was quantitative research. The research population was 252 employees and the sample was 72 respondents sampled by simple random sampling technique and the data collection method used questionnaire. The data analysis was multiple regression analysis, t test and F test using SPSS 24. Based on the analysis result on the effect of selection on employee performance in the Jakarta Headquarter of Suzuki Finance Indonesia, there was no positive and significant effect. Therefore, h1 was rejected and h0 accepted. As for the effect of placement on employee performance in the Jakarta Headquarter of Suzuki Finance Indonesia, there was positive and significant effect. Therefore, h2 was accepted and h0 was rejected. Meanwhile, the effect of selection and placement on employee performance in the Jakarta Headquarter of Suzuki Finance Indonesia was positive and significant. Therefore, the hypothesis was proven.